Parametric Analysis of Steel Studs to Reduce Thermal Bridges in Light Steel Framing Construction Systems - Marcelo Langner; Thais A. Soares; António Figueiredo; Ricardo M. S. F. Almeida; Romeu Vicente (Buildings)
Thermal bridges significantly affect the thermal performance of light steel framing systems due to the high thermal conductivity of steel. The objective of this study is to identify modifications on the steel profiles to reduce heat flux and improve the thermal resistance of both single- and double-layer wall panels. Three approaches were analyzed: (i) slotted steel studs, (ii) integration of less-conductive materials into the web section, and (iii) modifications to web geometry. A numerical model was calibrated based on experimental data and used to perform dynamic simulations with different configurations. Results show that incorporating less-conductive materials, such as rigid polyamide, achieved a heat flux reduction of up to 98%, while optimized slotted patterns reduced heat flux by up to 90%. The results also demonstrated that all web modifications effectively reduced heat flux through the wall, with approaches (i) and (ii) showing the greatest impact. The shape of the slots also has an important impact on the heat flux. The most effective strategy for enhancing the thermal performance of the steel studs was the use of a less-conductive material.